Genetic Structure and Evolutionary History of Rhinopithecus roxellana in Qinling Mountains, Central China - Li, Yuli; Huang, Kang; Tang, Shiyi; Feng, Li; Yang, Jia; Li, Zhonghu; Li, Baoguo (Frontiers in Genetics, 2021)
The Qinling Mountainous region is one of the world’s biodiversity hotspots and provided refuges for many endangered endemic animals. The golden snub-nosed monkeys (Rhiniopithecus roxellana) are considered as a flagship species in this area. Here, we depicted the genetic structure and evolutionary history via microsatellite markers and combination with the ecological niche models (ENMs) to elucidate the intraspecific divergent and the impacts of the population demography on our focal species. Our results revealed three distinct subpopulations of R. roxellana, and also uncovered asymmetric historical and symmetric contemporary gene flow existed. Our evolutionary dynamics analyses based on DIYABC suggested that the intraspecific divergence accompanied with effective population sizes changes. The ENMs result implied that the distribution range of this species experienced expansion during the last glacial maximum (LGM). Our results highlighted that geological factors could contribute to the high genetic differentiation within the R. roxellana in the Qinling Mountains. We also provided a new insight into conservation management plans with endangered species.